Beta-glicosidases das famílias GH 1 e GH 3 : caracterização estrutural, bioquímica e mecanismos estruturais de transglicosilação - Florindo, Renata Nobrega (2016)
The search for new sustainable alternative energy sources has followed the increasing concerns with common welfare and fossil fuel shortage. In this context, Bioethanol is a good option and lignocellulosic biomass is an interesting way of obtaining it. The enzymatic conversion of lignocellulosic biomass in fermentable sugars still is a costly process, which makes characterization mechanisms indispensable to make it economically viable. Being of great importance in the lignocellulosic biomass convertion, β-glucosidases catalyzed reaction is the last step in the saccharification processes. Beta glucosidase hydrolyze non-reduced β-D-glycoside terminals, releasing β-D-glucose. GH 1 and GH 3 are the families of those most studied enzymes. However, structural and functional data from this GH 3 family of enzymes are still scarce. This work aimed at the biochemical and structural characterization of β-glucosidase from Bifidobacterium adolescentis (BaBgl). This enzyme has a catalytic domain (CCD) and a fibronectin III-like domain (FnIII) whose function is still unknown. Biochemical data showed optimal conditions for enzyme activity at pH from 6.0 to 6.5, temperature at 45 ° C and synthetic substrate specificity of 4-nitrophenyl- -Dglucopyranoside (pNPG). The values of kinetic parameters, KM and Vmax, were 0.32±0.03 mM e 0.37±0.01 nmol/min, respectively. The enzyme doesn’t have transglycosylation mechanisms, indicating only hydrolytic activity. Some monosaccharides such as xylose and galactose increased the enzyme activity significantly, while glucose and arabinose inhibited it. The crystal structural model of the BaBgl revealed an N-terminal domain with fold like a TIM barrel, an intermediate sandwich α / β domain and a third C-terminal like FnIII domain. In this work we also studied the transglycosylation mechanisms of two β-glucosidases from Trichoderma harzianum (ThBgl1 and ThBgl2). Both enzymes exhibit transglycosylation reaction but the ThBgl1 showed a hydrolysis/transglycosylation ratio lower than the one for ThBgl2. Crystallographic structures shows a typical folding for GH family 1 β-glucosidases, folding in the form of a TIM barrel (α / β)8. However, ThBgl2 has a more polar active site and therefore, favorites the interaction with water molecules, promoting better the hydrolysis reaction when compared to ThBgl1.